HOW GOVERNMENT ACCOUNTING STANDARDS AND INTERNAL CONTROL SYSTEMS INFLUENCE GOOD GOVERNANCE WITH THE USE OF INFORMATION TECHNOLOGIES AS MODERATING VARIABLES - Dang Panagaman Tamba; Lainatusshifa Kemal (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Government Accounting Standards (GAS) and Internal Control Systems (ICS) on good governance at the Food Security and Livestock Service of North Sumatra Province, Indonesia; evaluate the role of information technology utilization as a moderating variable that can strengthen the relationship between the implementation of GAS and ICS on good governance; and analyze how good governance can accelerate rice self-sufficiency in the region. This research employed a mixed method with a sample of 40 employees at the Food Security and Livestock Service of North Sumatra Province. The qualitative data were processed from the NVivo software, while the quantitative approach was analyzed using Partial Least Squares (PLS) and the SmartPLS software with descriptive statistical tests, outer model analysis, inner model analysis, and hypothesis testing. Data analysis results on the influence of government accounting standards and internal control systems on good governance, with the use of information technology as a moderating variable, which most often appears using NVivo software on a word cloud, include control, reports, finance, internal, government, accounting, effectiveness, and accountability. PLS analysis results show that the use of information technology as a moderating variable can influence government accounting standards on good governance, and the use of information technology as a moderating variable is unable to influence the internal control system on good governance.